Seasonal variations of phsycio-chemical characteristics of Jamgavan dam water of Hingoli District (M.S.) India. - V, Waghmare N; D, Shinde V; R, Surve P; E, Ambore N (International Multidisciplinary Research Journal, 2012)
Jamgavan dam is a minor irrigation dam. The water in Jamgavan dam is used for irrigation, fish culture, drinking and domestic purposes. The present investigation deal with the study of seasonal variations of physicochemical characteristics of Jamgavan dam water. The study was carried out during the year 2007 for a period of 12 months. The parameters such as atmospheric temperature, water temperature, pH, free carbon dioxide, Electrical conductivity and dissolved oxygen were studied.